A newly recognized clade of Pleurothallis with Mesoamerican distribution - Wilson, M.; Pupulin, F.; Archila Morales, F. L.; Damon, A.; Solano Gómez, R. (Lankesteriana: International Journal on Orchidology, 2013)
.